Variations in costs and use of provincially-funded testosterone replacement therapy across Canada: a population-based study. (1st November 2016) - Tadrous, Mina; Martins, Diana; Lee, Kathy; Knowles, Sandra; Mamdani, Muhammad M.; Juurlink, David N.; Gomes, Tara
ABSTRACT: Introduction : Provincial drug-program policies for the reimbursement of testosterone replacement therapy (TRT) vary across Canada, which may result in marked regional variability in use. Methods : We conducted a population-based cross-sectional analysis of provincially funded TRT spending and utilization in eight provinces across Canada in 2012. We reported the annual cost per user, total cost, and rate of use of TRT overall and by formulation. Results : We identified 23, 544 provincially-funded recipients of TRT in 2012 in the eight provinces studied. Average annual cost per person varied by 3-fold, ranging from $173 (Prince Edward Island) to $485 (Ontario). Ontario also had the highest rate of use (1, 105 users per 100, 000 eligible) and the most liberal listing. Provinces with more restricted access (Alberta, British Columbia, and PEI) had lower annual costs per user ($293, $206, $173, respectively). Conclusions : Differing reimbursement policies for TRT products across Canada are likely contributing to variation in the rate of use and cost per recipient.